2021
DOI: 10.3390/buildings11050209
|View full text |Cite
|
Sign up to set email alerts
|

FRP Cables to Prestress RC Beams: State of the Art vs. a Split Wedge Anchorage System

Abstract: Versatility and high performance in terms of specific stiffness and strength, as well as non-corrosive sensitivity, make FRP (Fiber-Reinforced Polymer) cables a viable alternative to steel ones in the development of prestressing systems. On the other hand, the orthotropic and brittle nature of FRPs could trigger a premature failure of the cable in the anchorage system, for which several solutions have been proposed so far in civil structural applications. In this context, after a preliminary state of the art, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…According to the literature, anchorages for FRP cables can be divided into bonded and mechanical, which contain the split-wedge systems. A review of bonded anchorages is provided in [11], while principles are illustrated in [30], where a hybrid bonded/splitwedge anchorage is also presented. Split-wedge anchorages are composed of (Figure 1): (1) an external tapered-steel barrel; (2) two or more wedges and (3) the FRP cable, often protected by metallic sleeves (made of aluminum or copper), which envelope the cable portions arranged inside the wedges.…”
Section: Conceptualization and Review Of Split-wedge Anchoragesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, anchorages for FRP cables can be divided into bonded and mechanical, which contain the split-wedge systems. A review of bonded anchorages is provided in [11], while principles are illustrated in [30], where a hybrid bonded/splitwedge anchorage is also presented. Split-wedge anchorages are composed of (Figure 1): (1) an external tapered-steel barrel; (2) two or more wedges and (3) the FRP cable, often protected by metallic sleeves (made of aluminum or copper), which envelope the cable portions arranged inside the wedges.…”
Section: Conceptualization and Review Of Split-wedge Anchoragesmentioning
confidence: 99%
“…Focusing on split-wedge systems for FRP cables, modifications to the traditional anchorages for steel tendons are requested due to their high tilting angles, usually in the order of 5-7 • [22] and small anchoring lengths. The experimental tensile test [11] on a CFRP tendon blocked through a traditional anchorage highlighted the premature slippage of the cable. Improvements proposed in the literature so far mainly concerned the shape of barrel/wedge interface, that governs the magnitude and distribution of the stress components on the cable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhuge (2010) also evaluated the stress of a conical barrel based on the mechanical behavior of the wedge-type anchor for CFRP tendons. Campbell et al (2000) observed the performance and changes in the wedge for individual and cyclic loads based on the wedge-type stainless steel anchorage system using FRP tendons [ 22 , 23 , 24 , 25 , 26 ]. Thus, most existing studies have focused on the wedge-type anchorage system using steel strands [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Damiani et al [9] proposed an original split wedge anchorage for fiber-reinforced polymer (FRP) cables to prestress existing RC members for structural rehabilitation purposes. A remarkable literature review of FRP cables is reported, including the short-and long-term effects of mechanical properties for aramid-, glass-, and carbon-fiber-based cables.…”
mentioning
confidence: 99%